2009
DOI: 10.1111/j.1742-7843.2008.00345.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sri Lankan Black Tea (Camellia sinensis L.) on Pregnancy of Rats

Abstract: The aim of this study was to demonstrate the potential effects of black tea brew of Camellia sinensis using Sri Lankan high grown dust grade no. 1 tea on pregnancy outcome of rats when exposed during early (days 1-7), mid (days 8-14) and late (days 15-21) pregnancy of rats. Different doses of black tea brew (mg/ml/day) was orally administered daily during this period to separate groups of rats (n ¼ 6/group): 84 (equivalent to 1.5 cups), 167 (3 cups), 501 (9 cups), and 1336 (24 cups). The results showed that bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 11 publications
(16 reference statements)
0
9
0
Order By: Relevance
“…Black tea brew, which naturally contains caffeine, has been demonstrated to produce no risk in terms of pregnancy outcome in rats (Ratnasooriya et al 2009). No adverse effects have been noted even upon treatment with high doses corresponding to the consumption of 24 cups/day in humans.…”
Section: Combined Exposurementioning
confidence: 99%
“…Black tea brew, which naturally contains caffeine, has been demonstrated to produce no risk in terms of pregnancy outcome in rats (Ratnasooriya et al 2009). No adverse effects have been noted even upon treatment with high doses corresponding to the consumption of 24 cups/day in humans.…”
Section: Combined Exposurementioning
confidence: 99%
“…Many research studies have shown that caffeine readily crosses the placenta causing teratogenic and embryotoxic effects [6,7,8]. Also shown are the adverse effects of high doses of caffeine ingested during pregnancy, both for the mother and the developing foetus [9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Since then, a number of studies have confirmed the negative effect of high doses of caffeine ingested during pregnancy both for the mother and the developing foetus [2,3,7,15,16,18,22,25,27,30,31].…”
Section: Introductionmentioning
confidence: 99%